(untitled) (GIST – Education and Learning Research Journal, 2019)
The following paper describes the outcomes and insights of the first stage of an action research study aimed to explore ways in which CBP and NC strengthen sense of community and provoke actions to benefit that community is a public school located in a rural area. This work emerged from a needs analysis study in which students gave their opinions about the importance of English as a second language. Implementing CBP and Negotiated Syllabus as means to involve and foster students to be aware of their responsibility for the preservation of the school facilities, as well as educating the surrounding community, demonstrated the development of sense of community in the students. Throughout the use of questionnaires, surveys and journals, the outcomes revealed that students felt more motivated when they are taken into account in making curricular decisions. In addition, this study showed that a commitment from the entire academic community is possible when some academic and personal goals are established collaboratively and efforts are made to generate important changes. Keywords: Sense of Community, Community Based Project, negotiated syllabus, needs analysis, critical pedagogy.